The Comparison Between the MLE and Standard Bayes Estimators of the Reliability Function of Exponential Distribution - Ali, Mohammed Jamel; Gorgees, Hazim Mansoor (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2019)
In this paper, a Monte Carlo Simulation technique is used to compare the performance of MLE and the standard Bayes estimators of the reliability function of the one parameter exponential distribution.Two types of loss functions are adopted, namely, squared error loss function (SELF) and modified square error loss function (MSELF) with informative and non- informative prior. The criterion integrated mean square error (IMSE) is employed to assess the performance of such estimators .